Association of insulin resistance surrogate indices and erectile dysfunction: a systematic review and meta-analysis - Sayeh Jalali; Negar Zareshahi; Amir Hossein Behnoush; Alireza Azarboo; Amirhossein Shirinezhad; Seyyed Yasin Hosseini; Amin Javidan; Amirhossein Ghaseminejad-Raeini (BMC, 2024)
Abstract Background Erectile dysfunction (ED) has been linked to insulin resistance (IR), with various surrogate indices being used to assess this association. This systematic review and meta-analysis aimed to evaluate the relationship between IR indices and the incidence and severity of ED. Methods A comprehensive search across PubMed, Embase, Web of Science, and Scopus was carried out. Required data were extracted and meta-analyzed. The Newcastle-Ottawa Scale (NOS) was employed to evaluate the studies' risk of bias. Sensitivity analyses and meta-regressions were conducted to explore heterogeneity and the impact of confounding variables. Results Seventeen studies with a total of 3810 patients with ED and 8252 without ED were included. Meta-analysis revealed that males with ED had significantly higher levels of Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) (SMD = 0.59, 95% CI [0.15, 1.03], I2 = 82%, P < 0.01), Triglyceride-Glucose Index (TyG) (SMD = 0.53, 95% CI [0.31, 0.75], I2 = 69%, P < 0.01), and Visceral Adiposity Index (VAI) (SMD = 0.45, 95% CI [0.25, 0.64], I2 = 76%, P < 0.01) compared to those without ED. However, there was no significant correlation between a one-unit increase in HOMA-IR (OR = 0.63, 95% CI [0.03, 13.69], I2 = 91%, P = 0.77) or TyG (OR = 0.53, 95% CI [0.02, 11.53], I2 = 88%, P = 0.68) and the odds of ED. Additionally, a one-unit increase in VAI was associated with more severe ED (SMD = 0.34, 95% CI [0.03, 0.64], I2 = 16%, P = 0.03). The diagnostic accuracy of these indices varied. Conclusions The results indicate a significant connection between insulin resistance and erectile dysfunction, as shown by HOMA-IR, TyG, and VAI. Yet, their usefulness in predicting ED is restricted because of significant differences and inconsistencies in diagnostic precision. More research is required to determine the clinical importance of these indices in treating ED.